Effect of exchange transfusion on elimination of antibiotics in premature infants - Özkan, Hasan; Çevik, Necla (The Turkish Journal of Pediatrics, 1994)
Although the use of exchange transfusion has become routine in intensive care nurseries, little information is available on drug loss resulting from exchange transfusion. The aim of this study was to review the effect of exchange transfusion on the elimination of some antibiotics in premature infants according to the recent pharmacokinetic data. A pharmacokinetic equation was used to estimate drug loss from the body by exchange transfusion. Our data suggest that exchange transfusion can significantly decrease the serum concentrations of antibiotics with smaller volumes of distribution, but the drug loss of antibiotics with larger volumes of distribution can be acceptable.